2017
DOI: 10.1093/ee/nvx040
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns and Sequential Sampling Plans for Predators of Aphis glycines (Hemiptera: Aphididae) in Minnesota Soybean

Abstract: The soybean aphid, Aphis glycines Matsumura, is an economically important soybean pest. Many studies have demonstrated that predatory insects are important in suppressing A. glycines population growth. However, to improve the utilization of predators in A. glycines management, sampling plans need to be developed and validated for predators. Aphid predators were sampled in soybean fields near Rosemount, Minnesota, from 2006-2007 and 2013-2015 with sample sizes of 20-80 plants. Sampling plans were developed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…The foliar-foraging community of predators was dominated by O. insidiosus . This finding is consistent with a previous report from soybean fields in Minnesota (Tran and Koch 2017). Similarly, O. insidiosus and Araneae were the most prevalent foliar-foraging predators in soybean fields in southeastern Virginia (Whalen et al 2016).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The foliar-foraging community of predators was dominated by O. insidiosus . This finding is consistent with a previous report from soybean fields in Minnesota (Tran and Koch 2017). Similarly, O. insidiosus and Araneae were the most prevalent foliar-foraging predators in soybean fields in southeastern Virginia (Whalen et al 2016).…”
Section: Discussionsupporting
confidence: 94%
“…The community of foliar-foraging predators was assessed through visual whole-plant inspections (modified from Tran and Koch (2017)). On each sample date, 10 plants were selected from each location.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies are still rare though, and an additional challenge is that NEETs require modelling and computer skills. Tran and Koch (2017) determined the spatial patterns of predators of a pest aphid. Decision support systems are considered to be necessary for implementation of NEETs, as otherwise turning sampling results into decisions is too complicated.…”
Section: Natural Enemy Adjusted Thresholds (Neets)mentioning
confidence: 99%
“…Simulations were performed by randomly selecting samples with replacement from the validation data sets until the corresponding stop line was exceeded. If resulting average precision values were better than the desired precision values, desired precision was relaxed to obtain the average desired precision (Burkness and Hutchison 1997, Galvan et al 2007, Tran and Koch 2017. Resampling analysis to determine the sample sizes required to attain the desired precision was based on 500 resampling iterations of each data set.…”
Section: Required Sample Size For Population Estimatesmentioning
confidence: 99%
“…3B, Table 5). During resampling simulations, average achieved precision exceeded the desired level of 0.25, so desired precision was relaxed to 0.28 to achieve an empirical precision of 0.25, as was performed by Burkness and Hutchison (1997), Galvan et al (2007), and Tran and Koch (2017). Similarly, results based on the average of the samples used for validation showed that an ASN of 40 sets of 25 sweeps would be required to achieve a desired precision of 0.25 for stink bug densities ranging from 0.05 to 10.4 stink bugs per 25 sweeps (mean of 1.8 stink bugs per 25 sweeps; Fig.…”
Section: Required Sample Size For Population Estimatesmentioning
confidence: 99%